2022
DOI: 10.1007/s11192-022-04266-0
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for quality in data integration systems: a completeness-aware integration approach

Abstract: Ensuring the quality of integrated data is undoubtedly one of the main problems of integrated data systems. When focusing on multi-national and historical data integration systems, where the “space” and “time” dimensions play a relevant role, it is very much important to build the integration layer in such a way that the final user accesses a layer that is “by design” as much complete as possible. In this paper, we propose a method for accessing data in multipurpose data infrastructures, like data integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…is approach allows the user to prepare all the maximum information available from an integrated data system without the need for preliminary data quality analysis of each database contained within it. A case study by Daraio C on research infrastructure for scientific and innovative research demonstrated the usefulness of the proposed approach [6]. Dalla Valle and Kenett proposed a new data integration method that can calibrate online generated big data using interview-based customer survey data.…”
Section: Related Workmentioning
confidence: 99%
“…is approach allows the user to prepare all the maximum information available from an integrated data system without the need for preliminary data quality analysis of each database contained within it. A case study by Daraio C on research infrastructure for scientific and innovative research demonstrated the usefulness of the proposed approach [6]. Dalla Valle and Kenett proposed a new data integration method that can calibrate online generated big data using interview-based customer survey data.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the relevance of the issue, many authors have proposed methods or guidelines to assess problems on data quality [6][7][8][9][10][11][12][13]. However, few works focus on the problems that specifically regards the case of numerical data describing repeated observations of the same units over a period of time.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to avoid time-consuming manual database browsing. A relational database's entries, rows, and columns can easily be increased or decreased without affecting any of the relevant applications (Al-Saffar et al, 2018;Hu, et al, 2018).Creation of relationships among tablesRelationships between tables are the most important aspect of the architecture, as this is where the power of a relational database is realized(Le et al, 2013;Boguslawski et al, 2015;Breunig et al, 2020;Mekala et al, 2020;Daraio et al,2022). The present study compiled a set of metadata describing each Feature, attribute, and sub-attributes used to ease the development of a unified database.…”
mentioning
confidence: 99%